Most recent risky drinking session with Australian teenagers - Lam, T.; Lenton, Simon; Ogeil, R.; Burns, L.; Aiken, A.; Chikritzhs, T.; Gilmore, W.; Lloyd, B.; Wilson, J.; Lubman, D.; Mattick, R.; Allsop, S. (Wiley-Blackwell Publishing Asia, 2016)
© 2016 Public Health Association of Australia.Objective: Despite declines in Australian alcohol consumption, youth alcohol related harms remain prevalent. These alcohol-related consequences appear to be driven by a subset of risky drinkers who engage in 'high intensity' drinking episodes and are underrepresented in national health surveys. This project aims to investigate high risk drinking practices and alcohol-related harms amongst young people not otherwise recorded in existing data. Methods: A community sample of the heaviest drinking 20-25% 16-19 year olds were surveyed across three Australian states (n=958; 80% metropolitan). We examined the context of their last risky drinking session through online and face-to-face surveys. Results: Males consumed a mean of 17 and females 14 standard drinks, and 86% experienced at least one alcohol-related consequence during this session. More than a quarter of the face-to-face sample had Alcohol Use Disorders Identification Test (AUDIT) scores indicative of alcohol dependence. Indications of dependence were 2.3 times more likely among those who felt uncomfortable about seeking alcohol treatment, and less likely if harm reduction strategies were frequently used while drinking. Conclusions: It is clear this underrepresented population experiences substantial acute and potentially chronic consequences. Implications: Within the context of increasing alcohol-related harms among young Australians, the understanding of this group's drinking habits should be prioritised.